Evaluation of Spawning- and Natal-Site Fidelity of Larimichthys polyactis in the Southern Yellow Sea Using Otolith Microchemistry - Song, Dade; Xiong, Ying; Jiang, Tao; Yang, Jian; Zhong, Xiaming; Tang, Jianhua; Kang, Zhongjie (Frontiers in Marine Science, 2022)
Small yellow croaker Larimichthys polyactis is an important species with high commercial value, which migrates regularly among overwintering, spawning, and feeding, and grounds in coastal and marine waters. However, L. polyactis fidelity to natal or spawning sites is not well understood. This study used laser ablation inductively coupled plasma-mass spectrometry to analyse the elemental composition of otoliths from 60 adult yellow croakers caught in the southern Yellow Sea, including two spawning groups including one- and two-year-old fish (S1and S2, respectively) sampled close to China and one overwintering group including two-year-old fish (O2) sampled close to South Korea. The ratios of elements (Li, Na, Sr, and Ba) to Ca in the otolith core zone were significantly higher (P < 0.05) than those of the year one and year two annual rings (Y1 and Y2, respectively), but there were no significant differences in the elemental ratios between the Y1 and Y2 zones. Principal component analysis of the elemental otolith signatures of the core, Y1, and Y2 zones in the three groups revealed two distinct clusters (cluster 1: S1-core, S2-core, and O2-core zones; cluster 2: S2-Y1, O2-Y1, S2-Y2, and O2-Y2 zones) and one zone (S1-Y1), suggesting the existence of the spawning-site fidelity but not natal-site fidelity, especially considering the prolonged period (50 h) from fertilized eggs to hatching or yolk sac stages. Furthermore, these results indicated that the S2 and O2 groups could represent the same population, suggesting a stable migratory route for L. polyactis in Chinese and South Korean waters, whereas the S1 group could represent another population, suggesting there exist a mixed L. polyactis population in the southern Yellow Sea. Characterization L. polyactis spawning-site fidelity is a crucial step toward linking spawning-site fidelity of this overexploited species with thorough conservation and management strategies.